G379(P) Is a post-partum neonatal intensive care unit (nicu) admission necessary for all neonates with a prenatal diagnosis of congenital pulmonary airway malformation (cpam)?. (May 2019) - Dawson, I; Simcox, L
Abstract : Objective: To evaluate if a post-partum Neonatal Intensive Care Unit (NICU) admission is necessary in all neonates with a pre-natal diagnosis of Congenital Pulmonary Airway Malformation (CPAM). Methods: This retrospective case series analysed all CPAM cases referred to a tertiary centre in the North West of England from 2010–2018 using online databases. Results: There were a total of 101 cases referred to the unit. The pattern of CPAM lesions diagnosed reflected previous literature, with microcystic lesions diagnosed most frequently (50/101). The vast majority of cases had a positive outcome (92%), with high levels of surgical intervention noted (47%). Fetal hydrops was found to be a predictor of poor outcome. Sixty-four per cent of infants required less than forty-eight hours in NICU, where they were observed and received x-ray imaging. Neonates with longer NICU admissions were significantly more likely to require surgical intervention before six months of age (p=0.008). Conclusion: It could be argued that a sufficient level of care could be provided for the majority of CPAM infants on a general post-natal ward. A system would have to be implemented to ensure that NICU care remained available when required. Potential indicators for higher care include early signs of respiratory distress and sonographic evidence of fetal hydrops.